2000
DOI: 10.1086/313609
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Specific Pneumococcal Serogroups to Different Disease Manifestations: Implications for Conjugate Vaccine Formulation and Use, Part II

Abstract: To assess whether certain serogroups of Streptococcus pneumoniae are preferentially associated with specific disease manifestations, we analyzed all recent pneumococcal disease studies and assessed the relative frequency of isolation of each serogroup by clinical site (as a proxy for different disease states). In all age groups, serogroups 1 and 14 were more often isolated from blood, and serogroups 6, 10, and 23 were more often isolated from cerebrospinal fluid (CSF); in young children, serogroups 3, 19, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
185
4
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(203 citation statements)
references
References 48 publications
12
185
4
2
Order By: Relevance
“…Although any pneumococcal serotype may invade a sterile site, some serotypes seem to prefer particular locations. For instance, serotypes 1, 3, 5, 6A or 6B, 9V, 14, 19F, and 23F have been associated with invasive infections (2,4,6). In our patient, finding serotype 23B in the CSF was unusual, since it is rarely found among S. pneumoniae strains causing invasive infections.…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…Although any pneumococcal serotype may invade a sterile site, some serotypes seem to prefer particular locations. For instance, serotypes 1, 3, 5, 6A or 6B, 9V, 14, 19F, and 23F have been associated with invasive infections (2,4,6). In our patient, finding serotype 23B in the CSF was unusual, since it is rarely found among S. pneumoniae strains causing invasive infections.…”
mentioning
confidence: 52%
“…In our patient, finding serotype 23B in the CSF was unusual, since it is rarely found among S. pneumoniae strains causing invasive infections. In the study by Hausdorff and colleagues, serotype 23B was seldom found among serotypes that cause meningitis in Latin America (6). Similarly, in the analysis of 3,066 S. pneumoniae isolates from CSF derived from the Brazilian pneumococcal surveillance system, serotype 23B was identified in only 1% of isolates (2).…”
mentioning
confidence: 96%
“…On average, there are 4,100 cases of meningitis, 8 12,000 of bacteremia, 9 500,000 of pneumonia, and 7 million cases of otitis media annually in the United States. 10 , 11 The bacterium most commonly affects pediatric, elderly, and immunocompromised hosts. S. pneumoniae is the leading cause of pneumonia in children worldwide and is responsible for 30% of adult pneumonia cases.…”
Section: Characteristics Of the Bacteriummentioning
confidence: 99%
“…13,14 An average of 1.2 million young children worldwide die due to pneumococcal pneumonia and meningitis. 10 In developed countries, the mortality rate for pneumococcal pneumonia can reach 11–40%. 12 …”
Section: Characteristics Of the Bacteriummentioning
confidence: 99%
“…To optimize the formulation of conjugate vaccines and to evaluate the appropriateness of their use in various geographic areas and age groups, it was necessary first to understand the serogroup-specific epidemiology of S. pneumoniae. 100 Considering the large number of epidemiologic studies about pneumococcal serotype distribution worldwide, Hausdorff and colleagues performed several data analyses designed to reveal which pneumococcal serotypes should be included in conjugate vaccines. 101 The investigators analyzed more than 70 data sets to compare the serogroups causing IPD with those represented in conjugate formulations.…”
Section: Serotype Specificity Of Conjugate Vaccinesmentioning
confidence: 99%